2017
DOI: 10.1016/j.pmrj.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low‐Load Exercise on Postneedling‐Induced Pain After Dry Needling of Active Trigger Point in Individuals With Subacromial Pain Syndrome

Abstract: Background The application of dry needling usually is associated with postneedling‐induced pain. A postneedling intervention to reduce this adverse event is needed. Objective To determine the effectiveness of low‐load exercise on reducing postneedling‐induced pain after dry needling of active trigger points (TrPs) in the infraspinatus muscle in subacromial pain syndrome. Design A 72‐hour follow‐up, single‐blind randomized controlled trial. Setting Urban hospitals. Participants Individuals with subacromial pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
3
11
0
2
Order By: Relevance
“…Nevertheless, it is commonly seen in clinical practice that most patients usually recover from post-needling induced-pain/soreness between 48 and 72 hours after the intervention. This clinical observation has been confirmed in recent studies investigating the effects of some post-needling techniques, eg, spray andstretch,48 ischemic compression,49 or low-load eccentric exercise 50. All these studies found that these interventions were effective for decreasing post-needling induced pain/soreness 12 hours after TrP-DN application, but at 48 and 72 hours after, all patients were recovered from post-needling induced-pain independent of the post-needling intervention.…”
Section: Trigger Point Dry Needlingsupporting
confidence: 54%
“…Nevertheless, it is commonly seen in clinical practice that most patients usually recover from post-needling induced-pain/soreness between 48 and 72 hours after the intervention. This clinical observation has been confirmed in recent studies investigating the effects of some post-needling techniques, eg, spray andstretch,48 ischemic compression,49 or low-load eccentric exercise 50. All these studies found that these interventions were effective for decreasing post-needling induced pain/soreness 12 hours after TrP-DN application, but at 48 and 72 hours after, all patients were recovered from post-needling induced-pain independent of the post-needling intervention.…”
Section: Trigger Point Dry Needlingsupporting
confidence: 54%
“…Mild adverse events after DDN, including bruising, bleeding, or soreness, are considered very common [12]. The presence of postneedling soreness was observed in a high proportion of pain patients after deep DDN techniques of MTrPs in the neck region (91.4%) [13], shoulder (100%) [14], or low back (83%) [15]. The clinical relevance of postneedling soreness remains uncertain, but it has been associated with reduced treatment adherence [16,17] and it is considered capable of influencing patients’ functionality in daily life activities [18].…”
Section: Methodsmentioning
confidence: 99%
“…The clinical relevance of postneedling soreness remains uncertain, but it has been associated with reduced treatment adherence [16,17] and it is considered capable of influencing patients’ functionality in daily life activities [18]. Previous studies have investigated the effectiveness of various therapies to reduce postneedling soreness, including manual therapy [19,20], ultrasound [16], or exercise [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fresh amniotic membrane cannot be preserved for a long time, and potential biological safety hazards, such as hepatitis virus and HIV contamination, substantially limit its clinical use [23]. After dehydration and micronization of fresh amnion, Gellhorn prepared suspension before injection to treat tendonitis and arthritis and achieved good results in relieving pain and improving function [24].…”
Section: Discussionmentioning
confidence: 99%